Strain Difference in Photoreceptor Cell Death After Retinal Detachment in Mice - Matsumoto, Hidetaka (The Association for Research in Vision and Ophthalmology, 2014)
PURPOSE. To evaluate the potential for mouse genetic background to effect photoreceptor cell death in response to experimental retinal detachment (RD). METHODS. Retinal detachment was induced in three inbred mouse strains (C57BL/6, BALB/c, and B6129SF2) by subretinal injection of sodium hyaluronate. A time course of photoreceptor cell death was assessed by TUNEL assay. Total photoreceptor cell death was analyzed through comparing the outer nuclear layer (ONL)/inner nuclear layer (INL) ratio 7 days post RD. Western blot analysis or quantitative real-time PCR (qPCR) were performed to assess cell death signaling, expression of endogenous neurotrophin, and levels of apoptosis inhibitors 24 hours after RD. Inflammatory cytokine secretion and inflammatory cell infiltration were quantified by ELISA and immunostaining, respectively. RESULTS. The peak of photoreceptor cell death after RD was at 24 hours in all strains. Photoreceptor cell death as well as monocyte chemoattractant protein 1 and interleukin 6 secretion at 24 hours after RD was the highest in BALB/c, followed in order of magnitude by C57BL/6 and B6129SF2. Conversely, nerve growth factor expression and ONL/INL ratio were the lowest in BALB/c. Apoptosis signaling was higher in C57BL/6, whereas necroptosis signaling was higher in C57BL/6 and BALB/c. Autophagic signaling was higher in BALB/c. X-linked inhibitor of apoptosis (XIAP) and survivin protein levels were lower in C57BL/6 and BALB/c, respectively. Macrophage/microglia infiltration was higher in C57BL/6 and BALB/c at 24 hours after RD. CONCLUSIONS. Photoreceptor cell death after RD was significantly different among the three strains, suggesting the presence of genetic factors that affect photoreceptor cell death after RD.